The The Impact of Predatory Pricing on E-Commerce Competition and Regulatory Control in Indonesia - Shafira El Zahra; Farchanza Haykanna Pireno; Aurel Meidina Zammara; Pina Arohmah (Journal Social Sciences and Humanioran Review, 2024)
The increasing use of digital in society has encouraged digital transactions on many e-commerce platforms. This opens up great opportunities for digital entrepreneurs, but on the other hand, the increase in online shopping can also pose a serious threat to local entrepreneurs. Predatory pricing practices, which are often implemented by large companies with the aim of dominating the market, are one of the most obvious threats. Starting from the existing background, the author examines the formulation of the problem which includes how competition in the e-commerce market in Indonesia can be influenced by predatory pricing practices, and how regulations in Indonesia are regulated to supervise and control predatory pricing practices in the e-commerce sector. This study aims to analyze the impact of predatory pricing practices on competition in the e-commerce market in Indonesia and to examine existing regulations in overcoming these practices. The method used in this study is normative juridical with a literature study approach, which examines laws and regulations, related policies, and relevant literature. The results of the study indicate that predatory pricing practices can disrupt market competition by harming consumers in the long term even though they can provide lower prices initially. Although regulations such as Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition already exist, the implementation of supervision of predatory pricing practices in the e-commerce sector is still limited and requires adjustment to technological developments.